Is frequency of tooth brushing a risk factor for periodontitis? A systematic review and meta-analysis - Zimmermann, Heiko; Zimmermann, Nils; Hagenfeld, Daniel; Veile, Annette; Kim, Ti-Sun; Becher, Heiko (Community dentistry and oral epidemiology, 2015)
Objectives The epidemiology of periodontitis regarding oral‐hygiene practices particularly the frequency of tooth brushing has been the subject of relatively few dedicated studies. This paper provides a systematic review of available relevant epidemiological studies and a meta‐analysis of the effect of tooth brushing frequency on periodontitis. To review and to quantify the risk for periodontitis associated with frequency of tooth brushing. Methods Systematic literature search was conducted in nine online resources (PUBMED, ISI and 7 additional databases). Related and cross‐referencing publications were reviewed. Papers published until end of March 2013 reporting associations between tooth brushing frequency and periodontitis were considered. A meta‐analysis was performed to quantify this association. Results Fourteen studies were identified. The test of heterogeneity for cross‐sectional studies was not significant (P = 0.31). A fixed‐effects model yielded a significant overall odds ratio estimate of 1.41 (95%CI: 1.25–1.58, P < 0.0001) for infrequent compared to frequent tooth brushing. For all fourteen studies, there was a slight indication for heterogeneity (I² = 48%, P = 0.02) and the corresponding result with a random‐effects model was 1.44 (95%CI: 1.21–1.71, P < 0.0001). Conclusions There are relatively few studies evaluating the association between tooth brushing frequency and periodontitis. A clear effect was observed, indicating that infrequent tooth brushing was associated with severe forms of periodontal disease. Further epidemiological studies are needed to precisely estimate the effect of key risk factors for periodontitis and their interaction effects.